+0  
 
0
160
1
avatar+3027 

Help.

NotSoSmart  Jan 11, 2018
 #1
avatar+88898 
+2

3x^2 - 4 =  -x^4         add x^4 to both sides

 

x^4 + 3x^2  - 4  = 0     factor as

 

(x^2 + 4) (x^2 - 1)  = 0

 

(x^2 + 4)  (x + 1)  ( x-1)  = 0

 

Setting the last two factors to 0 and solving for x produces   x = -1 and x  = 1

 

Settting the first factor to 0, we have

 

x^2 +4  = 0   subtract 4 from both sides

 

x^2  =   -4         take both roots

 

x = ±√-4    =  ±2i

 

So the solutions are    1, -1, 2i, 2i

 

 

(s + 4v)^5  =

 

s^5  +  5(s^4)(4v) + 10(s^3)(4v)^2  + 10(s^2)(4v)^3  + 5(s)(4v)^4  + (4v)^5  

 

s^5  +  20s^4v  + 160s^3v^2   + 640s^2v^3  + 1280sv^4  +  1024v^5  [third answer ]

 

 

cool cool cool

CPhill  Jan 11, 2018

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.